2019
DOI: 10.1007/s11947-019-02365-0
|View full text |Cite|
|
Sign up to set email alerts
|

The inhibitory effect of chlorogenic acid on lipid oxidation of grass carp (Ctenopharyngodon idellus) during chilled storage

Abstract: Grass carp (Ctenopharyngodon idellus) is a kind of freshwater fish which is rich in polyunsaturated fatty acids and easily exposed to lipid oxidation during refrigeration. The effect of chlorogenic acid (CGA) on lipid oxidation, protein oxidation, enzymatic activities, and color stability of grass carp muscle during chilled storage was investigated. The lipid oxidation was inhibited by CGA, as evidenced by lower thiobarbituric acid values, peroxide values, carbonyl valence, less free fatty acid content, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Rosemary extract inhibited lipid oxidation by scavenging free radicals to stop the free radical chains. Similar antioxidant properties were observed with grape pomace flour [ 145 ], chlorogenic acid [ 166 ], and gelatin-polycaprolactone composite films combined with lysozyme and pomegranate PE [ 136 ].…”
Section: Traditional Methods Used To Evaluate Quality Changessupporting
confidence: 58%
See 1 more Smart Citation
“…Rosemary extract inhibited lipid oxidation by scavenging free radicals to stop the free radical chains. Similar antioxidant properties were observed with grape pomace flour [ 145 ], chlorogenic acid [ 166 ], and gelatin-polycaprolactone composite films combined with lysozyme and pomegranate PE [ 136 ].…”
Section: Traditional Methods Used To Evaluate Quality Changessupporting
confidence: 58%
“…One application has been to test the addition of natural preservatives with meat products, which have been investigated in a large number of studies. Some of these studies have already been discussed [ 27 , 136 , 145 , 164 , 165 , 166 ]. Other meat quality parameters, such as conjugated dienes (measured at 233 nm), protein carbonyl groups (measured at 370 nm), protein thiol groups (measured at 410 nm), or metmyoglobin (measured at 525, 572, and 730 nm), all of which reflect quality and acceptability can be measured by UV-Vis spectroscopy [ 195 , 200 ].…”
Section: Spectroscopic Monitoring Techniquesmentioning
confidence: 99%
“…TBARS were measured according to a former method [29]. Minced fish muscle (~5.00 g) was homogenized (IKA Ultra-Turrax T18 Basic, Staufen, Germany) with 25 mL 7.5% (w/v) trichloroacetic acid (containing 0.1% EDTA) for 1 min at 3000 rpm, then centrifuged (Fitchell SF-TDL-5A, Shanghai, China) at a speed of 4000 g for 5 min.…”
Section: Thiobarbituric Acid Reactive Substances (Tbars) and Ph Analysismentioning
confidence: 99%
“…However, there are very few studies that have demonstrated the application of grass carp preservation in the field. Recently, we found that CGA showed good efficiency in inhibiting lipid oxidation of grass carp muscle during chilled storage (Cao, et al, 2019). However, the mechanism of action of CGA and mode of inhibition of lipid oxidation during fish preservation is still not yet clear.…”
Section: Introductionmentioning
confidence: 99%